EXPLORING THE INTERSECTION OF SHARIA AND SUFISM IN IMĀM RABBĀNĪ AḤMAD SIRHINDĪ’S MAKTŪBĀT RABBĀNĪ: A CRITICAL ANALYSIS - Chowdury, Saeyd Rashed Hasan (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
with a particular focus on the writings of Imām Rabbānī Aḥmad Sirhindī as articulated in Maktūbāt Rabbānī. While specific Islamic reformist movements posit a fundamental dichotomy between these two domains, Sirhindī contends that sufism and sharia are inseparable, with the former serving as an extension of the latter. This research seeks to analyze Sirhindī’s reconciliation of Islam’s mystical and legal dimensions, demonstrating that proper spiritual purification must occur within the framework of sharia rather than in opposition to it. Methodologically, this study employs a qualitative approach, utilizing textual analysis of Maktūbāt Rabbānī, particularly its first three volumes—to explore Sirhindī’s discourse on the necessity of legal adherence in the spiritual journey. The research also engages in comparative analysis with the works of Ibn al-‘Arabī, al-Ḥallāj, and al-Ghazālī to contextualize Sirhindī’s position within broader sufi thought. The findings reveal that Sirhindī’s model of tasawwuf is rooted in doctrinal orthodoxy, critiquing mystical deviations that detach spirituality from religious law. The study concludes that Sirhindī’s work offers a systematic framework for understanding sufism within Islamic jurisprudence, challenging perspectives that perceive a dichotomy between mystical practice and legal adherence. By addressing contemporary misconceptions, this research contributes to ongoing debates on the role of spirituality in Islamic law, reaffirming Maktūbāt Rabbānī as a seminal text in the discourse on the harmonious integration of sharia and tasawwuf.